2022
DOI: 10.1186/s12902-022-01145-w
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin lowers serum calcium levels in lithium-users: results from a randomized controlled trial

Abstract: Background Although lithium is considered the gold-standard treatment for bipolar disorder (BD), it is associated with a variety of major endocrine and metabolic side effects, including parathyroid hormone (PTH) dependent hypercalcemia. Aside from surgery and medication discontinuation, there are limited treatments for hypercalcemia. This paper will assess data from a randomized controlled trial (RCT). Methods This is a secondary analysis of an RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In terms of whether cholesterol could be driving hypercalcemia, there is some evidence. Two interventional studies using statins have shown reductions in calcium levels [ 49 , 50 ], whereas another single‐arm study showed declines that did not reach significance [ 51 ]. A Mendelian Randomization approach using LDL‐C as the instrument was also associated with elevated calcium levels [ 52 ], further supporting a potential causal relationship with cholesterol driving calcium levels.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of whether cholesterol could be driving hypercalcemia, there is some evidence. Two interventional studies using statins have shown reductions in calcium levels [ 49 , 50 ], whereas another single‐arm study showed declines that did not reach significance [ 51 ]. A Mendelian Randomization approach using LDL‐C as the instrument was also associated with elevated calcium levels [ 52 ], further supporting a potential causal relationship with cholesterol driving calcium levels.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of whether cholesterol could be driving hypercalcemia, there is some positive evidence. Two interventional studies using statins have showed a reductions in calcium levels [45,46], whereas another single-arm study showed declines that did not reach significance [47] . A Mendelian Randomization approach using LDL-C as the instrument was also associated with elevated calcium levels [48], further supporting a potential causal relationship with cholesterol driving calcium levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium therapy might lead to difficulties if it is used for an extended period. Even when lithium therapy has been stopped, prolonged lithium administration can cause irreversible nephrogenic diabetic insipidus [33,34]. The administration of DDAVP is ineffective because the primary problem is a nephron's insensitivity to ADH rather than a lack of ADH release [35].…”
Section: Nephrogenic DImentioning
confidence: 99%